Combining PUF with RLUTs : a two-party pay-per-device IP licensing scheme on FPGAs - Roy, Debapriya Basu (2020)
With the popularity of modern FPGAs, the business of FPGA specific intellectual properties (IP) is expanding rapidly. This also brings in the concern of IP protection. FPGA vendors are making serious efforts toward IP protection, leading to standardization schemes like IEEE P1735. However, efficient techniques to prevent unauthorized overuse of IP still remain an open question. In this article, we propose a two-party IP protection scheme combining the re-configurable look-up table primitive of modern FPGAs with physically unclonable functions (PUF). The proposed scheme works with the assumption that the FPGA vendor provides the assurance of confidentiality and integrity of the developed IP. The proposed scheme is considerably lightweight compared to existing schemes, prevents overuse, and does not involve FPGA vendors or trusted third parties for IP licensing. The validation of the proposed scheme is done on MCNC’91 benchmark and third-party IPs like AES and lightweight MIPS processors.